KERAGAMAN MORFOLOGI DAN GENOTIPE TANAMAN ROSELLA (Hibiscus sabdariffa L.) GENERASI M2 HASIL IRADIASI SINAR GAMMA - Amaluddin Syahputra (Jurnal Pertanian Tropik, 2017)
The aim of the research was to determine the genetic diversity and value inheritance on population distribution pattern M2 generation of Roselle (Hibiscus sabdariffa L.). The research was conducted at the Faculty of the Agriculture University of North Sumatra, Medan from September 2016 to March 2017. The data were analyzed using a t-analysis. The parameters observed were the percentage of germination, plant height, number of branches, canopy diameter, flower petal diameter, flower petal weight, fruit weight, number of flower petals per plant and harvest age. The results showed the population of 450 Gy generation M2 showed increasing crop productivity, while population 600 Gy generation M2 resulted in decreased productivity in plants and resulted in longer harvest age. The range of hereditability and genetic diversity coefficients ranging from medium to large is found in the number of branch characters in the population of 450 Gy, the flower weight of the petals, the weight of the fruit and the number of petals per plant in the population of 300 Gy, 450 Gy, and 600 Gy.